Fostering Project-Based Learning through Industry Engagement in Capstone Design Projects - Ashraf Badir; Robert O'Neill; Kristoph-Dietrich Kinzli; Simeon Komisar; Jong-Yeop Kim (MDPI AG, 2023)
Extensive studies have indicated that real-life project-based learning through industry involvement in capstone design courses provides benefits to students, faculty, and industry practitioners. This paper presents the contributions of industry participants to student experiential and project-based learning in the civil and environmental engineering senior design courses at Florida Gulf Coast University (FGCU). Surveys were conducted to obtain insights into the contributions of industry involvement in the capstone design course from the perspectives of both students and practitioners. Practitioners have been involved in various roles, including project mentors for capstone design projects and/or judges for students' capstone design project presentations. Practitioners, through the students, are provided with new ways of looking at and solving problems. Practitioners, through their involvement, provide valuable feedback to the faculty and students that enriches the overall experience gained in the capstone design course. This feedback helps improve student performance on their projects and provides them with additional tools to carry forward into their engineering careers. However, there was a gap in perception between students and practitioners with regard to the benefits of industry involvement. This paper also describes two successful capstone design projects and culminates success drivers from the reflection of instructors teaching these courses. The results of this study have substantial implications for faculty teaching these courses. They showed what students did well and pinpointed areas for improvement through the lens of industry practitioners.